2006
DOI: 10.1111/j.1365-2702.2006.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors which constrain nurses from research participation

Abstract: this study adds a qualitative perspective; although findings are not generalizable, they support quantitative study findings into this subject; identifies constraints that require to be overcome for practising nurses to actively get involved in research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 49 publications
13
122
0
Order By: Relevance
“…According to the results of present research, in terms of the individual restraining factors, lack of time due to job preoccupation has had the highest frequency in view of professors; this is consistent with results of the study of Tan M et al, Hemsley-Brown J et al and Roxburgh M. [20][21][22] This individual barrier can be caused by the multiple responsibilities of professors in the training, consulting, and executive and administrative areas in university environments. Engaging in executive and administrative activities, in addition to take a lot of valuable time of faculty members who can be spent on research and science production, has also this threat as a consequence that being continuous of staying in such posts creates gradually a kind of administrative tendency and routine in these individuals.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of present research, in terms of the individual restraining factors, lack of time due to job preoccupation has had the highest frequency in view of professors; this is consistent with results of the study of Tan M et al, Hemsley-Brown J et al and Roxburgh M. [20][21][22] This individual barrier can be caused by the multiple responsibilities of professors in the training, consulting, and executive and administrative areas in university environments. Engaging in executive and administrative activities, in addition to take a lot of valuable time of faculty members who can be spent on research and science production, has also this threat as a consequence that being continuous of staying in such posts creates gradually a kind of administrative tendency and routine in these individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Teaching that is only upon memorizing the texts and journals of the developed world is no doubt ineffective in solving problems of developing countries (King, 2004). On the other hand, researchers who conduct research in developing countries and having sufficient experience and motivation (Roxburgh, 2006), February 2015, Vol. 5, No.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical nurses are predominantly portrayed as having a positive attitude to research, many studies conducted on their utilization and participation in nursing research focus on the nurses' self-perceived barriers and deficiencies with respect to pursuing research in the clinical setting (Adamsen et al, 2003;Akerjordet et al, 2012;Breimaier et al, 2011;Brown et al, 2010;Carlson and Plonczynski, 2008;Chan et al, 2011;Higgins et al, 2010;McMaster et al, 2013;Roxburgh, 2006). Breimaier et al (2011) conducted a selfreport questionnaire study of 1023 Austrian hospital nurses, and found three main barriers to research utilization to be lack of time (70%), lack of information and/or knowledge (46%) and lack of interest (26%).…”
Section: Introductionmentioning
confidence: 99%